OPTIMALISASI KEBIJAKAN PEMBANGUNAN TENAGA KERJA INDUSTRI KULIT MELALUI PENDIDIKAN VOKASI INDUSTRI - Risang Pujiyanto (Politeknik ATK Yogyakarta, 2017)
The National Industrial Development Master Plan 2015-2035 states that the availability of competent workforce is one of the most influential things in national industrial development. Vocational education is one of the solutions to create a workforce that suits the needs of the industry. The problems that occur are how the labour policy and industrial labor policy in Indonesia and how to optimize the policy development of industrial workers at Polytechnic of ATK Yogyakarta. This research is normative law research, with statute approach. The results show that both the Major Labour Law and the Industrial Law, regulate the increase of the competence of the workforce. In relation to the development of leather industry workers at Polytechnic of ATK Yogyakarta, various policies such as National Higher Education Standards, Indonesia National Qualification Framework, Indonesian National Working Competency Standards, Profession Certification, Student-Based Learning can support the creation of competent leather industry workforce. By optimizing the policy, it is expected that competent leather industry workers can be created to support the development of national industry.